A flexible data hiding scheme using differential dual mapping - Femi, D; Thylashri, S; Ravikumar, S (International Journal of Engineering and Technology, 2018)
Steganography is the approach with invisible communication. In our proposed system maximum of 3000 characters can be embedded in the image which is chosen from a video and a different type of frame work for hiding and extracting are provided at both nodes. As an extension of this work, the same algorithm can be implemented in three channels of the colour image. A lossless data hiding technique based on the differential pair mapping algorithm by embedding data bits in an image is proposed, then a generated image is embedded with large amount of data in the form of bits in the mean-removed via the proposed algorithm. Experimental outputs shows that stego-image in our method has high capacity and security with certain robustness and the PSNR value is higher than the other techniques.